Smart Farming System for Monitoring and Optimizing Paddy Field with Internet of Things Technology - Bagus Adhi Kusuma; Sarmini Sarmini; Wiga Maulana Baihaqi; Sitaresmi Wahyu Handani (Telematika, 2023)
Rice is a type of plant that is very easy to find, especially those who live in rural areas. Most people make rice as a source of staple food. One of them is in Bugel Sampang Hamlet, Central Java, where the agricultural sector of the village often experiences rice harvest failure due to dry weather. The hilly geographical conditions that do not allow irrigation systems are the main problem, while the soil fertility of the hamlet is relatively good, as a result farmers find it difficult to optimize the treatment dose for agricultural land due to dry weather which often makes harvest conditions less than optimal. From the problems described above, the researcher aims to create an internet of things-based prototype by integrating a realtime firebase cloud service database, so that farmers can monitor the condition of their rice fields in real time, as well as monitor the weather that can be accessed using a website-based system. The method used is to integrate a microcontroller with sensors, namely DHT11, soil moisture sensor, barometer or air pressure sensor, anemometer or wind speed sensor, rainfall sensor, raindrop sensor using Arduino Mega 2560 and NodeMCU. Then the sensor acquisition data on the Arduino Mega 2560 is sent to the NodeMCU Lua Wifi V3 ESP8266 ESP12 using a JSON variable to be sent to firebase with an internet connection. The prototype has gone through thirty days running tests, while testing the information system using blackbox testing with data from the firebase realtime database. The results of the study concluded that the prototype was able to monitor the condition of the land properly and the system worked well and could support the optimization of farmers in the treatment of rice fields, so that the use of fertilizers, water, and other treatment efforts became more efficient.